2013
DOI: 10.1103/physrevd.87.123511
|View full text |Cite
|
Sign up to set email alerts
|

Modeling halo mass functions in chameleonf(R)gravity

Abstract: On cosmological scales, observations of the cluster abundance currently place the strongest constraints on f (R) gravity. These constraints lie in the large-field limit, where the modifications of general relativity can correctly be modeled by setting the Compton wavelength of the scalar field to its background value. These bounds are, however, at the verge of penetrating into a regime where the modifications become nonlinearly suppressed due to the chameleon mechanism and cannot be described by this linearize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(197 citation statements)
references
References 59 publications
(82 reference statements)
10
185
2
Order By: Relevance
“…Lombriser et al (2013) found that haloes in f(R) gravity can be well described by the NFW formula (equation 11). In this work, we have further confirmed this by explicitly checking the χ 2 goodness-of-fit, in which we found that equation (11) works almost equally well in GR and f(R) gravity (with marginally smaller χ 2 for haloes between ∼10 12 -10 13 h −1 M in f(R) gravity), though the concentration parameters can be different, as we shall show below.…”
Section: Mass Distribution Inside Haloesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lombriser et al (2013) found that haloes in f(R) gravity can be well described by the NFW formula (equation 11). In this work, we have further confirmed this by explicitly checking the χ 2 goodness-of-fit, in which we found that equation (11) works almost equally well in GR and f(R) gravity (with marginally smaller χ 2 for haloes between ∼10 12 -10 13 h −1 M in f(R) gravity), though the concentration parameters can be different, as we shall show below.…”
Section: Mass Distribution Inside Haloesmentioning
confidence: 99%
“…In particular, the curves are smoother and better behaved when using M 200 , which may be because the FOF haloes are too irregular in their shapes and gravity is enhanced with different efficiency in different parts of the haloes, which can contaminate the screening effect expected for ideal spherical haloes (see e.g. Li & Efstathiou 2012;Li & Lam 2012;Lombriser et al 2013;Lombriser, Koyama & Li 2014, for more discussion about the expected behaviour of the f(R) halo mass function).…”
Section: Halo Mass Functionsmentioning
confidence: 99%
“…However, the difference between even |f R0 | = 10 −5 and ΛCDM is dwarfed by the difference between the theoretical volume fraction and the N-body result at all smoothing scales. This provides a quantitative basis for the assertion in [13] that there is insufficient evidence to warrant modelling the environemnt density using the f (R) equations. …”
Section: Volume Fractionsmentioning
confidence: 99%
“…A more accurate expression for the screening factor, which we will use in this paper, was derived in [13] from results in [15,26]. The gravitational force on a test-particle at the surface of a top-hat overdensity of radius R TH collapsing in an expanding background is given by…”
Section: Review Of Modified Gravitymentioning
confidence: 99%
See 1 more Smart Citation